Positive Aspects and Potential Drawbacks of Implementing Digital Teaching/Learning Scenarios in Health Professions Using Nursing Education as an Example: A Research Report from Germany - Lydia Pfeifer; Sophia Fries; Alexander Stirner; Lisa Nagel; Christian Cohnen; Leona Aschentrup; Marleen Schönbeck; Annette Nauerth; Patrizia Raschper; Tim Herzig; Kamil J. Wrona (MDPI AG, 2024)
Background: Learning arrangements in health care profession education are increasingly taking place in digital environments. Virtual reality (VR) in nursing education, as a digital element, is the subject of controversial debate. On one hand, it supports the authenticity of case studies by adding realistic perspectives and information. On the other hand, the costs of developing and maintaining software and hardware hinder its long-term implementation. Based in the German context, our aim is to promote the adoption of innovative digital methods in nursing education and to offer invaluable experiences from the field. Methods: In this paper, we describe our findings and insights from two different research projects focused on the incorporation of digital tools, particularly VR, into nursing education. Results: Starting with a brief recapitulation of the projects, we elucidate pedagogical strategies for embedding VR-driven scenarios in nursing education. Based on our experiences during the projects, we identify various positive aspects, such as changing perspective and simulating acute situations. Key findings: Although potential drawbacks remain, we advocate the long-term implementation and specific use of VR at the interface between theory and practice. Nevertheless, it is crucial to establish regular evaluation, observing the value of digitalisation, especially VR, for nursing education.